2021
DOI: 10.2147/ndt.s285863
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Migraine in Postmenopausal Women: A Systematic Review

Abstract: Introduction: Migraine prevalence is higher in fertile than in postmenopausal women. However, few literature data are available on the prevalence and characteristics of migraine after the menopause and on the effect of hormones in postmenopausal women with migraine. Methods: We performed a systematic literature review of studies available on Scopus and Web of Science from the beginning off indexing until October 18th, 2020. We included both randomized trials and observational studies. Results: We included 12 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Migraine occurrence can be affected by menstruation, pregnancy, and menopause, in addition to the use of hormonal contraceptives and hormone replacement therapies ( 39 ). In this regard, a recent systematic review of 12 studies showed that high-estrogen levels, high estrogen fluctuations, and hormonal replacement therapy were associated with the worst migraine outcomes ( 42 ).…”
Section: Biological Risk Factors and Comorbiditiesmentioning
confidence: 99%
“…Migraine occurrence can be affected by menstruation, pregnancy, and menopause, in addition to the use of hormonal contraceptives and hormone replacement therapies ( 39 ). In this regard, a recent systematic review of 12 studies showed that high-estrogen levels, high estrogen fluctuations, and hormonal replacement therapy were associated with the worst migraine outcomes ( 42 ).…”
Section: Biological Risk Factors and Comorbiditiesmentioning
confidence: 99%
“…Gender differences in migraine primarily depend on sex hormones. The high fluctuations in estrogen levels that accompany the menstrual cycle and perimenopause are associated with a possible exacerbation of migraine, leading to the particularly higher prevalence of migraine in women than in men during the female fertile period [ 39 41 ]. On the other hand, male sex hormones are likely protective against migraine, as suggested by the cessation of migraine in women treated with testosterone for reasons other than their migraines [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…After natural menopause, migraine usually improves [ 28 , 29 ], while women undergoing surgical menopause have a high risk of migraine worsening, possibly due to a sudden fall in estrogen levels [ 30 , 31 ]. The proportion of women reporting postmenopausal migraine worsening is particularly high in headache clinics, possibly due to selection bias [ 9 , 32 ]. Therefore, headache clinics likely provide care to a high proportion of women with perimenopausal migraine worsening, and women with previously rare migraines can come to the attention of a headache center for the first time because of a perimenopausal worsening.…”
Section: The Burden and Unmet Needs Of Women With Menstrual And Perimenopausal Migrainementioning
confidence: 99%
“…HRT is usually prescribed to reduce the vasomotor symptoms associated with the menopausal transition [ 100 , 101 ]. However, population-based studies suggest that HRT worsens migraine [ 32 , 102 , 103 ]. To limit migraine worsening after the menopause, different strategies are viable based on the estrogen withdrawal hypothesis, including the continuous rather than intermittent administration of combined hormonal treatments [ 104 ], the intrauterine or transdermal rather than oral administration of estrogen [ 105 ], and the administration of non-estrogen compounds such as tibolone [ 106 ].…”
Section: Considerations On the Treatment Of Perimenopausal Migrainementioning
confidence: 99%